FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN JAMBAN DI DESA PINTU LANGIT JAE KECAMATAN PADANGSIDIMPUAN ANGKOLA JULU TAHUN 2012 - Ikhsan Ibrahim; Devi Nuraini Santi; Taufik Ashar (Lingkungan dan Kesehatan Kerja, 2013)
Factors associated with the use of latrines in Desa Pintu Langit Jae Kecamatan Padangsidimpuan Angkola Julu 2012.  The most fundamental relathionship eith the quality of the environment in terms of laterine is the availability of facilities and the type of storage used faces. The use of latrines with family participation will be good, when supported by a number of factors. Among the factors that come from inside or outside the individual referred to internal factors such as education, knowledge, attitudes, actions while external factors such as the condition of latrines and water supply. This research aimed to investigate factors associated with the use of latrines in Desa Pintu Langit Jae Kecamatan Padangsidimpuan Angkola Julu 2012. This research used a descriptive analitic design method to look at the relationship of knowledge, attitudes, latrines conditions and cline water to the action latrine utilization using cross sectional study with interviews using questionnaires to 75 respondents who selected systemic sampling. The results showed that there was a significant association between the use of latrines with knowledge (p=0,000), there was a significant association between the use of latrines with attitude (p=0,000), there was a significant association between the use latrines with latrines condition (p=0,030) and there was a significant association between the use of latrines with availability of clean water in latrine (p=0,038). Expected for health workers in Desa Pintu Langit Jae kecamatan Padangsidimpuan Angkola Julu it provides on the importance of using latrines properly through conseling to community so that community have the knowledge and attitudes about self responsibility and the environment. Keyword : Knowledge, Attitudes, Latrines conditions, Water availability, Utilization latrines